The echiuran fauna of southern Africa (Class: Echiura, Phylum: Annelida) - Biseswar, Ramlall (African Zoology, 2019)
This paper is a comprehensive report on the genera and species of Echiura previously recorded from southern Africa south of 23°30' S. The echiuran fauna of this region currently comprises five genera and 22 species belonging to the single family Echiuridae. Three new species and six new records have been reported from the southern African region. The species of echiurans currently known from southern Africa have been reported from the east and south coasts and a very small part of the west coast extending northwards from Cape Town to Langebaan Lagoon. No records are as yet available from the coast of Namibia. Listriolobus capensis appears to be an endemic species, because it has not been recorded beyond the limits of southern Africa. Four species require additional investigation owing to their cosmopolitan status. A checklist of all the genera and species of echiurans recorded from southern Africa and a map showing their distribution along the coastline are given. A key for the identification of all the genera and species is provided. The museum accession numbers of all the species recorded from southern Africa are given.
World Polychaeta Database (WPolyDb)